Noble gases in Dome C micrometeorites: an attempt to disentangle asteroidal and cometary sources - Baecker, Bastian; Ott, Uli; Trieloff, Mario; Engrand, Cécile; Duprat, Jean (Icarus, 2022)
We have performed a comprehensive noble gas study, including the isotopes of krypton and xenon, on a set of micrometeorites (MMs) collected from surface snow at Dome C (DC) on the Antarctic plateau. He and Ne are generally dominated by a solar component, with lower 4He concentrations and 4He/20Ne ratios in crystalline (Xtal) compared to fine-grained carbonaceous (FgC) MMs. Concentrations of (surface-correlated) solar wind (SW) He and Ne in FgC MMs are at the high end of what has been seen in earlier work, whereas the abundances of (volume-correlated) Kr and Xe are similar to what has been found in previous studies of MMs. In most samples, isotopic ratios for Kr and Xe are in the usual range of Q-Kr and -Xe (the Q component is the dominating component in primitive macroscopic meteorites) and air. When quantifiable, cosmic ray exposure (CRE) ages based on cosmogenic 21Ne and 3He, in combination with the Poynting-Robertson effect, are broadly consistent with an origin of the MMs from the asteroid belt. An exception is an Xtal MM, which exhibits a cosmogenic 21Ne concentration in agreement with an origin from beyond Saturn, consistent with a possible cometary origin. In addition, data for trapped noble gases in three (out of ten analyzed) DC MMs provide hints that these may be related to a cometary source. One sample, a fragment of a FgC MM, is of particular interest. This fragment exhibits a Xe composition, although with large analytical uncertainties, deficient in the heavy isotopes 134Xe and 136Xe. This is similar to the Xe isotopic pattern, probably related to cometary ice, measured by Rosetta in the coma of comet 67P/Churyumov-Gerasimenko. The same MM also has an unusually high 36Ar/38Ar ratio, consistent with Rosetta's Ar measurement (in this case the latter having a large uncertainty). The other hints are for two MMs, of crystalline (Xtal) type, that show Ne similar to that found in laboratory analysis of refractory grains captured from comet 81P/Wild 2 by the Stardust mission. Additionally, a FgC/Xtal MM may contain excess 3He, similar to what has been seen in some cluster interplanetary dust particles (cluster IDPs).
Available online 12 January 2022
Gesehen am 24.06.2022